2014
DOI: 10.1007/s00404-014-3416-0
|View full text |Cite
|
Sign up to set email alerts
|

Routine use of EmbryoGlue® as embryo transfer medium does not improve the ART outcomes

Abstract: Routine use of EmbryoGlue(®)as a HA enriched ET medium for cleavage stage embryos does not have advantage to the conventional one for infertile patients undergoing ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Reports have suggested that adding HA to the ET medium can increase the IR and PR . Furthermore, the current findings corroborate the results reported by other studies that concluded HA may have beneficial effects in patients with RIF . Taken together, the aforementioned studies suggest the addition of HA to the transfer medium in patients with RIF significantly increases the IR and PR, while not affecting ectopic pregnancy and abortion rates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Reports have suggested that adding HA to the ET medium can increase the IR and PR . Furthermore, the current findings corroborate the results reported by other studies that concluded HA may have beneficial effects in patients with RIF . Taken together, the aforementioned studies suggest the addition of HA to the transfer medium in patients with RIF significantly increases the IR and PR, while not affecting ectopic pregnancy and abortion rates.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have indicated that HA‐enriched medium can improve the IR and clinical PR . In contrast, other studies have reported no beneficial effects of HA …”
Section: Introductionmentioning
confidence: 99%
“…6 Several authors state that HA-enriched media have not shown significant results in their study 2,19 and concluded that future research should show whether EG is the highest quality option for all patients or only for those patients in whom the quality of the embryo is poor, for patients in whom implantation has failed and older patients. 20 Nishihara et al 21 state that pregnancies, implantation, and abortion rates where media with different concentrations of HA was used during ET gives similar results.…”
Section: Discussionmentioning
confidence: 96%
“…17 A retrospective study conducted by Safari et al showed no significant advantage to using EmbryoGlue in embryo transfer media for good prognosis patients (live birth rate: p ¼ 1.0, n ¼ 229), and suggested that it may have more success in poor prognosis patients (RIF, poor-quality embryos, and advanced age. 18 EmbryoGlue is indicated for use in patients with RIF and advanced age (>35 years), with studies showing improved implantation and clinical pregnancy rates (odds ratio [OR]: 1.28; 1.43, 95% confidence interval [CI]: 1.03-1.59, n ¼ 1,282). 19 HETM is purported to improve implantation and pregnancy rates in patients undergoing frozen embryo transfer (FET), with the effect dependent on the number of previous FETs.…”
Section: Recent Evidencementioning
confidence: 99%